Geomorphic impact and rapid subsequent recovery from the 1996 Skeióarársandur jökulhlaup, Iceland, measured with multi-year airborne lidar - Smith, Laurence C.; Sheng, Yongwei; Magilligan, Francis J.; Smith, Norman D.; Gomez, Basil; Mertes, Leal A. K.; Krabill, William B.; Garvin, James B. (DigitalCommons@University of Nebraska - Lincoln, 2006)
The November 1996 jökulhlaup that burst from the Vatnajökull ice cap onto Skeiðarársandur was the highest-magnitude flood ever measured on the largest active glacial outwash plain (sandur). Centimeter-scale elevation transects, measured from repeat-pass airborne laser altimetry missions flown in 1996 (pre-flood), 1997, and 2001, show that sediment deposition exceeded erosion across the central Skeiðarársandur and established an average net elevation gain of +22 cm for the event. Net elevation gains of +29 and +24 cm occurred in braided channels of the Gígjukvísl and Skeiðará rivers, respectively. Nearly half of these gains, however, were removed within 4 years, and the two rivers contrast strongly in style of erosional/depositional impact and subsequent recovery. In the Gígjukvísl, the 1996 jökulhlaup caused massive sediment deposition (up to ~12 m) near the ice margin and intense “mega-forming” of braided channels and bars downstream. Post-jökulhlaup recovery (1997–2001) was characterized by rapid erosion (-0.5 m) of ice-proximal sediments and their transport to downstream reaches, and eradication of the mega-forms. In contrast, the Skeiðará displays minimal post-jökulhlaup sediment erosion in its upstream reaches and little change in braided channel relief. This contrast between river systems is attributed to the presence of a previously studied ~2-km wide ice-marginal trench, caused by glacier retreat and lowering, which contained flows of the Gígjukvísl but not the Skeiðará prior to dispersal onto the outwash plain. Rapid removal of jökulhlaup deposits from this trench suggests that in terms of long-term evolution of the sandur, such features only delay downstream migration of jökulhlaup-derived sediment. These results, therefore, suggest that the net geomorphic impact of jökulhlaups on surface relief of Skeiðarársandur, while profound in the short term, may be eradicated within years to decades.